2009
DOI: 10.1097/tp.0b013e3181a2a4b3
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G is a Crucial Immunosuppressive Molecule Secreted by Adult Human Mesenchymal Stem Cells

Abstract: Adult bone marrow-derived mesenchymal stem cells (MSCs) are multipotential cells capable of regenerating injured tissues. In addition to their multipotency, MSCs inhibit natural killer cell cytotoxicity and T-lymphocyte alloproliferation. Several immunosuppressive mechanisms have been described, including indoleamine 2, 3, -dioxygenase-induced depletion of tryptophan from the lymphocyte environment, and the secretion of prostaglandin E2 and other immunosuppressive factors. Here, we review data supporting a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 22 publications
2
86
1
Order By: Relevance
“…We specifically examined the correlation between MSC licensing and T cell cytokine suppression with MSC expression of galectin-9 (34), TRAIL (35), HLAG (36), TNFR (37), SLAM2 (38), HLAC (39), OX40L (40), CD200R (41), FASL (42), and B7H1/B7DC (26). Among these, we identified and validated B7H1 and B7DC as the sole inhibitory contact factors deployed by IFN-g licensing (26).…”
Section: Discussionmentioning
confidence: 99%
“…We specifically examined the correlation between MSC licensing and T cell cytokine suppression with MSC expression of galectin-9 (34), TRAIL (35), HLAG (36), TNFR (37), SLAM2 (38), HLAC (39), OX40L (40), CD200R (41), FASL (42), and B7H1/B7DC (26). Among these, we identified and validated B7H1 and B7DC as the sole inhibitory contact factors deployed by IFN-g licensing (26).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] However, the precise mechanisms underlying MSC-mediated immunosuppression remain largely undefined. Soluble factors such as hepatocyte growth factor (HGF), transforming growth factor (TGF)-β, 19,20 indoleamine 2,3-dioxygenase (IDO), 21 IL-2 and IL-10, 22 prostaglandin E2 (PGE2), [23][24][25] soluble HLA-G, 26 nitric oxide (NO), 27 immune cells (regulatory T cells), 28 as well as contact dependent mechanisms, 29,30 have been involved in MSC-mediated immunosuppression. In a previous study 8 we demonstrated that CD271-MSCs elicited a potent allosuppression even at low concentrations, and that the majority of the immunosuppressive effect of CD271-MSC haematologica | 2013; 98(10) is mediated via PGE2, but not via HLA-G, NO or IL-10 molecules.…”
Section: Discussionmentioning
confidence: 99%
“…48 MSCs use a variety of different factors in order to suppress immune responses, many of which are secreted. Some of these factors are constitutively produced by MSCs, such as HLA-G5, 49 prostaglandin E 2 (PGE 2 ), 50 and galectins. 51 The immunomodulatory effects exerted by MSCs can be augmented if the cells are activated by cytokines such as IFN-g. [52][53][54] It has also been shown that MSCs can be activated by stimulation of their Toll-like receptors.…”
Section: Immune Modulation By Mscsmentioning
confidence: 99%